Effect of hydroalcoholic extract of Myracrodruon urundeuva All. and Qualea grandiflora Mart. leaves on the viability and activity of microcosm biofilm and on enamel demineralization - Juliana Gonçalves Pires; Aline Silva Braga; Flaviana Bombarda de Andrade; Luiz Leonardo Saldanha; Anne Lígia Dokkedal; Rodrigo Cardoso de Oliveira; Ana Carolina Magalhães
Abstract Objectives: The aim of this study was to assess the effect of Myracrodruon urundeuva All. and Qualea grandiflora Mart. leaves hydroalcoholic extracts on viability and metabolism of a microcosm biofilm and on enamel demineralization prevention. Methodology: Microcosm biofilm was produced on bovine enamel using inoculum from pooled human saliva mixed with McBain saliva, under 0.2% sucrose exposure, for 14 days. The biofilm was daily-treated with the extracts for 1 min. At the end, it was analyzed with respect to viability by fluorescence, CFU counting and extracellular polysaccharides (phenol-sulphuric acid colorimetric assay) and lactic acid (enzymatic assay) production. The demineralization was measured by TMR. The data were compared using ANOVA or Kruskal-Wallis (p<0.05). Results: M. urundeuva All. at 100, 10 and 0.1 μg/mL and Q. grandiflora Mart. at 100 and 0.1 μg/mL reduced biofilm viability similarly to positive control (chlorhexidine) and significantly more than the negative-vehicle control (35% ethanol). M. urundeuva at 1000, 100 and 0.1 μg/mL were able to reduce both lactobacilli and mutans streptococci CFU counting, while Q. grandiflora (1000 and 1.0 μg/mL) significantly reduced mutans streptococci CFU counting. On the other hand, the natural extracts were unable to significantly reduce extracellular polysaccharides and lactic acid productions neither the development of enamel carious lesions. Conclusions: The extracts showed antimicrobial properties on microcosm biofilm, however, they had no effect on biofilm metabolism and caries protection.